Achieving democracy : the future of progressive regulation - Shapiro, Sidney A., 1947-; Tomain, Joseph P., 1948- (New York : Oxford University Press, 2014)
'Achieving Democracy' explains and explores the dynamic and changing nature of contemporary government and the future of the regulatory state. In a critique of the last 30 years of neoliberal government in the United States, Sidney A. Shapiro and Joseph P. Tomain demonstrate how to regain essential democratic losses, under a successful framework of a progressive government, to ultimately construct a good society for all citizens.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on February 28, 2014).
Keywords: Trade regulation -- Philosophy; Administrative law -- United States